Effect of Excavation Dewatering on Adjacent Structures (University of Khartoum Engineering Journal, 2022)
The study aims to investigate the effect of dewatering technique on retained ground and adjacent existing structures in order to avoid any damages that may occur. The paper presents three cases of potential structure failure caused by ground settlement as a result of dewatering. Two current construction projects in Khartoum North were selected as a case study. The two projects are located near Blue Nile River where ground water table exists at shallow depths. Dewatering to reduce the groundwater level was carried out in the two sites to facilitate excavation works. The buildings and road pavements around the two sites suffered serious damages due to excessive differential settlements of the retained ground. The study results showed that there are numerous sources of risks associated with performing dewatering. Therefore, developing appropriate plan for dewatering before construction is essential to mitigate any adverse impacts and avoid risks.
Keywords: Damages; dewatering; effect; groundwater.